A frequency and beamwidth reconfigurable antenna based on liquid crystal for 5G millimeter waves - Peng Chen; Xinju Wang; Dan Wang; Zongsheng Gan; Yutong Yin; Haowei Zhang (Scientific Reports)
Abstract In this paper, a novel frequency and beamwidth reconfigurable antenna is proposed. The antenna features a 5-layer vertically stacked structure with the dimensions of $$22× 30× 7.768$$ $$\hbox {mm}^{3}$$ , and the layers from top to bottom are the radiating layer, the orientation layer, the liquid crystal (LC) layer, the orientation layer, and the ground layer, and a liquid crystal cavity integrated into the LC layer. An inverted microstrip feed line structure is employed as the bias electrode, and connecting it to a coaxial line side-feed adapter for excitation of the antenna. To investigate the beamwidth reconfigurability, two parasitic dipole structures-all disconnected or connected-are placed on either side of the main radiating element for comparative analysis. Experimental results reveal that the antenna’s resonance frequency shifts from 31.78 GHz to 27.1 GHz, providing a frequency reconfigurable range of 14.73%. Notably, this frequency tuning process is minimally influenced by the type of parasitic patch. Additionally, the impedance bandwidth and -3dB beamwidth of the antenna remain largely unaffected by the reconfiguration. Testing the antenna with different parasitic patch structures, the -3dB beamwidth of the antenna expands from $$47^{° }$$ to $$92^{° }$$ at $$ε _r = 2.7$$ for the LC, and from $$53.5^{° }$$ to $$81^{° }$$ at $$ε _r = 3.1$$ , and the antenna peak gain of 6.04 dBi and 7.58 dBi, separately. These results correspond to a reconfigurable range of 64.75% and 40.89% for the -3dB beamwidth, respectively.